Perencanaan Skenario Menggunakan Soft-System Dynamics Methodology untuk Mengidentifikasi Ketahanan Badan Usaha Milik Desa - Muhammad Setiawan Kusmulyono (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
This study is a perpetuation of the action research process carried out at Bumdesa Mitra Cibogo Sejahtera in Cisauk District, Tangerang Regency. This study was performed to understand the future of bumdesa performance in the village by considering aspects of past and current performance. The application of the principle of scenario planning is a relevant way to provide options for describing potential scenarios without disturbing the performance of the observed bumdesa unit. This scenario planning adapts the soft system dynamics (SSDM) methodological approach which is considered to be able to accommodate problematic situations in villages that deal more with human beings. The observed village conditions are problematic because bumdesa has a strategic role and a strong relationship with the authority of the village head. The outcome of the scenario planning described in the matrix map show that the condition of Cibogo Village can choose the optimistic option because of the strong support of the village head and the agile performance of the bumdesa. The potential analysis of the results of this scenario can be a reference for the needs analysis of Bumdesa Mitra Cibogo Sejahtera to identify asset and resource needs in the future.